Intensitas Aroma dan Rasa Manis Kopi Siap Minum Berdasarkan Persepsi Konsumen dari Penggunaan Perisa Karamel dan Vanila - Faisal, Andrian Ibnu; Wijaya, Christofora Hanny; Hunaefi, Dase (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Ready-to-drink (RTD) coffee products typically contain high levels of sugar. Adding a sweet flavor enhancer can be an alternative to sugar reduction, preserving the sweetness consumers prefer. This study aimed to investigate the effect of sweet aroma flavorings on consumers' perceived sweetness intensity of RTD coffee. This study was conducted in four stages: (1) an initial survey for panelists screening, (2) a threshold detection test of vanilla and caramel flavorings performed in a laboratory test model using the 2-alternative forced choice (2-AFC) method, (3) just about right (JAR) test to determine the flavor concentration, and (4) an intensity rating test of aroma and sweetness and hedonic rating test to determine consumer panelists preferences. Responses were analyzed for ANOVA and Principal Component Analysis using IBM® SPSS® Statistics 26, XLSTAT, and GraphPad software. Based on survey results, 105 of 522 respondents volunteered to serve as panelists for the intensity and hedonic ratings. The flavor-detection threshold involved 74 consumer panelists; the detection thresholds for vanilla and caramel flavors in RTD coffee with 6% sugar content were 3 ppm and 4 ppm, respectively. As many as 70 consumer panelists participated in the JAR test. The highest JAR score for vanilla flavor was obtained at 75 ppm, and for caramel flavor at 100 ppm. Vanilla flavor at 75 ppm increased sweetness intensity by 9.8% and the sweet aroma by 14%. In contrast, the caramel flavor at 100 ppm did not significantly enhance either the sweetness or aroma intensity in RTD coffee. Based on consumer panelists' preferences, RTD coffee with vanilla flavor was most preferred over RTD coffee with caramel.